2020
DOI: 10.1002/pon.5314
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between post‐traumatic stress and post‐traumatic growth in cancer patients and survivors: A systematic review and meta‐analysis

Abstract: Objective: Research on the relationship between post-traumatic stress disorder (PTSD)/post-traumatic stress symptoms (PTSS) and post-traumatic growth (PTG) in cancer patients and survivors is increasing. Methods:We conducted a systematic review and meta-analysis of 51 studies that assessed the relationship between PTSD/PTSS and PTG, in cancer patients/survivors. Five databases were searched through 29 April 2019. The purpose of this manuscript is to report a summary of this literature, the aggregate effect siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
96
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 66 publications
9
96
2
Order By: Relevance
“…In terms of the regression analysis, shorter time since the cancer diagnosis, higher levels of general stress (i.e., higher PSS scores), and the occurrence of pain were significant predictors of membership in the stressed group. Although in a recent systematic review, 78 no association was found between time since cancer diagnosis and PTSD, this nonmodifiable characteristic may be used to identify high-risk patients. It is interesting to note that patients with higher scores on our measure of general stress were more likely to be in the stressed group.…”
Section: Discussionmentioning
confidence: 89%
“…In terms of the regression analysis, shorter time since the cancer diagnosis, higher levels of general stress (i.e., higher PSS scores), and the occurrence of pain were significant predictors of membership in the stressed group. Although in a recent systematic review, 78 no association was found between time since cancer diagnosis and PTSD, this nonmodifiable characteristic may be used to identify high-risk patients. It is interesting to note that patients with higher scores on our measure of general stress were more likely to be in the stressed group.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, metaanalyses investigating whether the results were moderated by measures assessing BF vs. PTG did not find an effect, suggesting that associations are largely comparable for BF and PTG. This metaanalytic evidence revealed as well that BF and PTG showed a small positive association with posttraumatic stress [5,7]. Furthermore, small associations were reported for enhanced positive well-being, while the association between BF or PTG and negative mental health as well as subjective physical health remains inconclusive [1,3].…”
Section: Introductionmentioning
confidence: 81%
“…9,10 Among those who have experienced traumatic events, the PTG of cancer patients has always been the focus of interest. 11,12 The factors of their PTG mainly relate to social support, the time and degree of illness, and coping style. [12][13][14] There has been little recent progress in identifying the influencing factors of PTG among people who fight against major infectious diseases, especially medical workers.…”
Section: Introductionmentioning
confidence: 99%